2021
DOI: 10.3389/fnagi.2021.741923
|View full text |Cite
|
Sign up to set email alerts
|

Liraglutide Reduces Vascular Damage, Neuronal Loss, and Cognitive Impairment in a Mixed Murine Model of Alzheimer’s Disease and Type 2 Diabetes

Abstract: Alzheimer’s disease is the most common form of dementia, and epidemiological studies support that type 2 diabetes (T2D) is a major contributor. The relationship between both diseases and the fact that Alzheimer’s disease (AD) does not have a successful treatment support the study on antidiabetic drugs limiting or slowing down brain complications in AD. Among these, liraglutide (LRGT), a glucagon-like peptide-1 agonist, is currently being tested in patients with AD in the Evaluating Liraglutide in Alzheimer’s D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 87 publications
2
7
0
1
Order By: Relevance
“…This GLP-1 agonist has also been shown to reverse memory impairment and synaptic loss in Aβ mouse models [ 106 ] with similar findings in nonhuman primate models [ 101 ]. Similar findings were observed in AD mouse models in the presence of T2D [ 107 , 108 ], suggesting multiple mechanisms underlying liraglutide’s neuroprotective benefits. Similar findings have been reported on another GLP-1 agonist, exendin-4, as it has been shown to increase brain insulin synthesis [ 109 ], to restore cerebral insulin signalling [ 110 ], to attenuate Aβ and tau pathology as well as neuroinflammation [ 111 , 112 , 113 ] and to improve cognition [ 113 ].…”
Section: Repurposing Diabetes Therapeutics For Alzheimer’s Diseasesupporting
confidence: 77%
“…This GLP-1 agonist has also been shown to reverse memory impairment and synaptic loss in Aβ mouse models [ 106 ] with similar findings in nonhuman primate models [ 101 ]. Similar findings were observed in AD mouse models in the presence of T2D [ 107 , 108 ], suggesting multiple mechanisms underlying liraglutide’s neuroprotective benefits. Similar findings have been reported on another GLP-1 agonist, exendin-4, as it has been shown to increase brain insulin synthesis [ 109 ], to restore cerebral insulin signalling [ 110 ], to attenuate Aβ and tau pathology as well as neuroinflammation [ 111 , 112 , 113 ] and to improve cognition [ 113 ].…”
Section: Repurposing Diabetes Therapeutics For Alzheimer’s Diseasesupporting
confidence: 77%
“…Liraglutide reduces by 40–50% the overall β-amyloid plaque count and dense-core plaque numbers, and by 50% the number of activated microglia in the cortex [ 161 ] and the hippocampus [ 162 ] of APP/PS1 mice. Liraglutide also exerts neuroprotective effects and reduces cortical microglia burden and number in the proximity of amyloid plaques in APP/PS1x db / db and APPswe/PS1dE9 mice [ 163 , 164 ]. It also reduces astrocytosis in APPswe/PS1dE9 mice [ 164 ].…”
Section: Anti-inflammatory Effects Of Glp-1r Activation In Neurodegen...mentioning
confidence: 99%
“…Cerebral microvascular impairments occurring in AD may reduce Aβ clearance. Some studies found liraglutide reduced incidence of cerebral microanuerysms and leakage ( 209 , 210 ).…”
Section: Neuroprotective Effects Of Glp-1r Agonistsmentioning
confidence: 99%